Bioactive goniothalamin from goniothalamus tapis with cytotoxic potential - Kallaya Sangrueng (2018)
© 2015 Kallaya Sangrueng, Saksri Sanyacharernkul, Sirinapa Nantapap, Narong Nantasaen and Wilart Pompimon. Goniothalamus (Annonaceae) is well known for the rich of styryllactone contents and these plants are famous for the potential to be applied as alternative biological activities. The chemical and biological investigations of Goniothalamus tapis is tested for anticancer activities. The research was processioned to extract, isolate, purify and elucidate structure from the leaves and twigs of G. tapis. The isolated compound was evaluated with cytotoxic activity. Goniothalamin was isolated from ethyl acetate extract of G. tapis and the spectroscopic techniques were used for structure elucidation. In addition, goniothalamin was the most powerful to cytotoxic activity which was the first reported for this specie. The goniothalamin was possessed a potent cytotoxicity. Therefore, it is possible to use this compound as a pharmacological agent.